1994
DOI: 10.1016/0014-5793(94)01118-4
|View full text |Cite
|
Sign up to set email alerts
|

PVP‐containing solutions for analysis of divalent cation‐dependent NMDA responses in Xenopus oocytes

Abstract: The electrophysiological analysis of Ca'+-conducting ion channels in Xenopus oocytes is difficult due to secondary intracellular effects induced by Ca 2+ . In the presence of polyvinylpyrrolidone (PVP) membrane currents can be recorded in nominally divalent cation-free solutions. The Ca2'-permeable recombinant NMDA receptors of the NRlMR2A subtype were used as assay system and the results show that PVP has no effect on NMDA receptor-induced currents. Ca" and Ba2' depress NMDA-induced currents at submillimolar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…As previously reported by Raditsch and Witzemann (1994), addition of 2 mM PVP to EGTA-containing, divalent-free Ringer's solution greatly reduced the membrane leak current and allowed for stable measurements of NMDA-induced currents to be made under these conditions. Figure 1 shows the effects of 100 mM ethanol on NR1/2A receptor currents measured in divalent cation-free PVP-Ringer' s solution.…”
Section: Ethanol Sensitivity Of Nmda Receptors In the Absence Of Divamentioning
confidence: 85%
“…As previously reported by Raditsch and Witzemann (1994), addition of 2 mM PVP to EGTA-containing, divalent-free Ringer's solution greatly reduced the membrane leak current and allowed for stable measurements of NMDA-induced currents to be made under these conditions. Figure 1 shows the effects of 100 mM ethanol on NR1/2A receptor currents measured in divalent cation-free PVP-Ringer' s solution.…”
Section: Ethanol Sensitivity Of Nmda Receptors In the Absence Of Divamentioning
confidence: 85%
“…3 C ) . Removal of the respective antagonist from the bathing solution revealed that receptors recovered (Raditsch and Witzemann, 1994). Stopping application of antagonist Me-D-AspR-mediated currents blocked by argiotoxin,,, (100 nM) recovered within 3 min up to 72% (a) whereas channels blocked by MK-801 (100 nM) showed only 27 % recovery during the same tiine (c).…”
Section: Resultsmentioning
confidence: 99%
“…Ba2+ (Leonard and Kelso, 1990) and polyvinylpyrrolidone 25, (Raditsch and Witzemann, 1994), were used in order to reduce Ca2+-evoked chloride currents in oocytes. Both agonists, glutamate (0.1 mM) and glycine (0.01 mM), were dissolved either in normal frog Ringer (NFR), or in modified, nominal Ca2+-free buffers such as BaZ+FR described above.…”
Section: Methodsmentioning
confidence: 99%
“…They are expressed in a broad variety of tissues and known to mediate fast synaptic transmission [7,8] and synaptic transmission between sympathetic nerves and smooth muscle [9,19]. By now 7 P2X receptor subunits (P2X!-P2X 7 ) have been cloned which share a putative two-transmembrane segment structure with intracellular C-and N-termini and an extracellular loop [2,3,5,6,14,20,21]. Heterologous expression of each subunit results in the formation of non-selective cation channels with differential sensitivities for the agonists ATP and a,|3-methylene-ATP and the antagonists pyridoxal-5-phosphate-6-azophenyl-2',4'-disulfonic acid (PPADS) and suramin.…”
Section: Introductionmentioning
confidence: 99%